The dilemma [large type] - Paris, B. A. (Wheeler Publishing large print hardcover, 2020)
"It's Livia's fortieth birthday, and her husband, Adam, is throwing her the party of a lifetime. Everyone she loves will be there, except her daughter, Marnie, who's studying abroad. But Livia is secretly glad that Marnie won't be there, because Livia has recently uncovered a stunning secret about her daughter. And while she's waiting until the party is over to tell Adam, he has his own surprise. Adam has arranged for Marnie to fly back for the party. When he hears some terrible news, Adam, too, is faced with a dilemma: Does he share what he's learned with his wife? How far are Adam and Livia willing to go to protect the loved ones, and give each other a few hours of happiness?"--Page 4 of cover.